Incorporating evolution into neuroscience teaching - Striedter, Georg F. (Frontiers in Education, 2023)
Neuroscience courses can be enriched by including an evolutionary perspective. To that end, this essay identifies several concepts critical to understanding nervous system evolution and offers numerous examples that can be used to illustrate those concepts. One critical concept is that the distribution of features among today's species can be used to reconstruct a feature's evolutionary history, which then makes it possible to distinguish cases of homology from convergent evolution. Another key insight is that evolution did not simply add new features to old nervous systems, leaving the old features unchanged. Instead, both new and old features have changed, and they generally did so along divergent trajectories in different lineages, not in a linear sequence. Some changes in nervous system organization can be linked to selective pressures (i.e, adaptation), especially if they occurred convergently in different lineages. However, nervous system evolution has also been subject to various constraints, which is why many neural features are, in a sense, suboptimal. An overarching theme is that evolution has brought forth tremendous diversity across all levels of the nervous system and at all levels of organization, from molecules to neural circuits and behavior. This diversity provides excellent research opportunities, but it can also complicate the extrapolation of research findings across species.